Fuzzy sets in management, economics, and marketing - Zopounidis, Constantin; Pardalos, P. M. (Panos M.), 1954-; Baourakis, George; International Association for Fuzzy-set Management and Economy (River Edge, N.J. : World Scientific, 2001)
The rapid changes that have taken place globally on the economic, social and business fronts characterized the 20th century. The magnitude of these changes has formed an extremely complex and unpredictable decision-making framework, which is difficult to model through traditional approaches. The main purpose of this book is to present the most recent advances in the development of innovative techniques for managing the uncertainty that prevails in the global economic and management environments. These techniques originate mainly from fuzzy sets theory. However, the book also explores the inte
Bank asset liability management techniques: An overview
English
"This book is prepared on the occasion of the 7th international congress of SIGEF, held in Chania, Greece"--Editorial.
Includes bibliographical references and index.
Keywords: Decision making -- Mathematical models; Marketing -- Decision making -- Mathematical models; Investments -- Decision making -- Econometric models; Fuzzy sets